(untitled) (Global Journal of Science Frontier Research, 2015)
Using a developed technique of synchronous differential temperature measurements, the existence of the thermal surface energy (TSE) has been demonstrated with a huge signal-tonoise ratio in material artifacts, made of a homogeneous material, when these artefacts are irradiated by an external electromagnetic (EM) field. The TSE, presenting the energy of the oriented motion of the coupled field-particles system inside a solid-state artifact, is shown experimentally to be linearly related to the Poynting vector of the external EM field, and it results in the appearance of the thermal hysteresis effect, which is irreversible in time and has no symmetry in spaceThe experiments, presented in this paper, have shown that the principle of superposition is not valid for EM fields in case of TSE, so that the thermal evolution process, which inevitably includes the changing in time and in space the variations of the thermal surface energy, is characterized by the infinite number of correlated influence factors.